The ROPO effect in the purchasing process - Zbońkowski, Michał (Udział efektu ROPO w procesie zakupu, 2020)
Nowadays new information technologies have transformed and influenced consumer behaviour; searching for information on the Internet is one of the most prevailing strategies in modern commerce. Due to the development of the Internet, the traditional sales model which entails making purchases on the basis of the information gathered in brick and mortar (traditional) stores is no longer dominant in most industries. The goal of this article is to present the intensity of the ROPO effect in the purchasing behaviour of Polish consumers in various industries and in different values. The paper involves the characteristics of the ROPO concept, a review of the main changes in the modern purchasing process and the presentation of the research results. The study indicated that the majority of clients obtain information from the Internet before making purchases in a brick and mortar shop. The conclusion of the article indicates the strategic implications resulting from the undertaken analysis, as well as directions for further research
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 3, s. 118-128
Keywords: ROPO effect; purchasing process; offline shopping; online shopping; omnichannel; efekt ROPO; proces zakupu; zakupy offline; zakupy on-line